Pengembangan Modul Elektronik Berbasis Model Learning Cycle 5E Pada Pembelajaran Kimia Materi Asam-Basa - Darsef Darwis; Ella Fitriani; Dian Styariyani (Jurnal Riset Pendidikan Kimia (JRPK), 2020)
The purpose of this reseacrh is to develop electronic module based on Learning Cycle 5E model on acid-base materials in chemistry learning. This research process used the ADDIE (Analysis, Design, Develop, Implementation, and Evaluation) research and development method. This research was conducted from December 2018 until June 2019. The research instrument that used ini this study are preliminary and needs questionnaire of students and teachers, media, material and language experts validation questionnaire, and trial test questionnaire on students and teachers. The expert validation of the electronic module was carried out by three material and language experts and media experts. The results of the material and language experts on the overall indicator obtained as good to excellent categories. The results of the media experts on the overall indicator obtained as good to excellent categories. Result of the product trial test to students and teachers on the overall indicator obtained with good to excellent categories. Based on the results obtained, it can be concluded that the devlopment of electronic module based on Learning Cycle 5E on acid-base materials is in accordance with students and teachers needs and has been eligible to be used in the learning process as a source of students learning.